IMPLEMENTATION OF SCIENTIFIC APPROACH THROUGH DISCOVERY LEARNING IN IMPROVING CRITICAL THINKING SKILLS OF NATURAL SCIENCE LEARNING AT THE FOURTH GRADE - HERIANINGTYAS, NUR LUTHFI RIZQA (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Nur Luthfi Rizqa Herianingtyas. Implementation of Scientific Approach through Discovery Learning in Improving Critical Thinking Skills of Natural Science Learning at the Fourth Grade. The objectives of this research are: (1) to describe the steps in implementing the Scientific Approach through Discovery Learning; (2) to improve students' critical thinking skills; and (3) to improve Natural Science learning outcomes. This research is a collaborative Class Action Research (CAR). Subjects were fourth grade students of SDN 1 Kebumen in academic year 2014/2015, totaling 39 students consisting of 21 male students and 18 female students. The experiment was conducted in third cycles. The results show that: (1) the implementation of Scientific Approach through Discovery Learning has been carried out by the following steps: (a) Orientation; (b) Problem Statement; (c) Data Collection; (d) Data Processing; (e) Verification; and (f) Generalization; (2) Natural Science learning outcomes is increased in Energy-Saving theme; and (3) can improve students' critical thinking skills in Natural Science learning.